Combined effects of aerodynamic and second-order hydrodynamic loads for floating wind turbines at different water depths. (January 2023) - Shi, Wei; Zhang, Lixian; Karimirad, Madjid; Michailides, Constantine; Jiang, Zhiyu; Li, Xin
Abstract: In this paper, fully coupled time-domain analysis of three different semisubmersible floating offshore wind turbines (semi-FOWTs) is performed. The focus of the present paper is to investigate the impact of second-order wave hydrodynamic loads combined with aerodynamic loads on the dynamic responses of semi-FOWTs under normal and extreme sea conditions. Three water depths (50, 100, and 200 m) are considered for examining the depth effect. The simulation results show that the second-order hydrodynamic loads play an important role in the motion and structural responses under extreme sea conditions irrespective of the inclusion of the aerodynamic loads in the analysis. Meanwhile, the aerodynamic loads significantly affect the dynamic responses of all semi-FOWTs under normal operational conditions. Among the three semi-FOWTs, the V-shaped semi-FOWT has the largest pitch motion responses under extreme sea conditions. Compared to the normal operation condition, the water depth has a larger impact on the motion and force responses of the three examined platforms under extreme sea condition. The surge and pitch motions decrease with water depth increases. The tower base loads tend to be lower for deep water depth, while the mooring line tensions are opposite. This findings could benefit the offshore wind turbine industries.